The impact of the work-family conflict on employee engagement, performance, and turnover intention - Ribeiro, Neuza (2021)
Purpose The incompatibility between the sphere of work and the family is a reality that plagues many workers today. The difficult articulation of these two domains leads to the experience of the phenomenon called work-family conflict (WFC). This paper aims to assess the impact that WFC may have on employee engagement and performance, as well as on their turnover intention. It is also intended to test the mediating effect of engagement on the relationship between WFC and performance, and between WFC and the turnover intention. Design/methodology/approach One hundred and sixty-seven employees from various Portuguese organizations were surveyed. Respondents reported their perceptions of own WFC, engagement, performance and turnover intention. Findings The results revealed that employees who feel a higher WFC have lower levels of engagement and greater intention to leave the organization. The WFC showed no relation to performance. Engagement takes on the mediating role in the relationship between WFC and the turnover intention. Practical implications The relevance of this study is related to the implications that it may bring to companies in the context of implementing work-family balance strategies to reduce the referred conflict. Originality/value This study contributes to WFC literature by attempting to integrate in the same model four concepts in a single study to provide a model that depicts the chain of effects between WFC, engagement, individual performance and turnover intention, which has never been done in the Portuguese context.